Subcellular Chemical Imaging: New Avenues in Cell Biology. Issue 3 (March 2020) - Decelle, Johan; Veronesi, Giulia; Gallet, Benoit; Stryhanyuk, Hryhoriy; Benettoni, Pietro; Schmidt, Matthias; Tucoulou, Rémi; Passarelli, Melissa; Bohic, Sylvain; Clode, Peta; Musat, Niculina
Abstract : To better understand the physiology and acclimation capability of the cell, one of the great challenges of the future is to access the interior of a cell and unveil its chemical landscape (composition and distribution of elements and molecules). Chemical imaging has greatly improved in sensitivity and spatial resolution to visualize and quantify nutrients, metabolites, toxic elements, and drugs in single cells at the subcellular level. This review aims to present the current potential of these emerging imaging technologies and to guide biologists towards a strategy for interrogating biological processes at the nanoscale. We also describe various solutions to combine multiple imaging techniques in a correlative way and provide perspectives and future directions for integrative subcellular imaging across different disciplines. Highlights: Chemical imaging instruments have substantially improved in sensitivity and spatial resolution and have become the method of choice to visualize and quantify elements, isotopes, and molecules at the subcellular level in various disciplines, such as cell biology, ecophysiology, and toxicology. Since chemical imaging provides low contrast, it is often combined with electron microscopy in a correlative way to unambiguously identify the localization of an element or molecule in the cell. Different complementary chemical imaging instruments (e.g., SIMS, X-ray fluorescence) can be combined to correlate elemental, isotopic, and molecular information from a region of the cell or from the entire cell in two or three dimensions. New sample preparation methods and analytical instruments enable indirect or direct correlative subcellular imaging from cells in their close-to-native state.